Development of a Turning Machine for a Windrow Composting Process of Oil Palm Empty Fruit Bunch - Suryanto, Hadi; Yahya, Azmi (2008)
A turning machine prototype has been designed to mix and to aerate oil palm empty fruit bunch (EFB) cuts composted in windrows. The machine was equipped with four wheels and a rotating drum with tines which enables it to move through a free – standing windrow of approximately 120 cm high by 220 cm across. The rear wheels and the rotating drum were hydraulically driven by a 54 hp engine. The turning machine was tested with EFB cuts and compost piled separately on a concrete floor. The average turning capacities for the EFB cuts and the compost were 22,020 kg/hr and 25,040 kg/hr respectively. At this setting, the average actual forward speeds of the machine were 104.4 m/hr for the EFB cuts and 75.0 m/hr for the compost. The wheel slips for these turning operations were almost constant at about 23%.